It's been a long day! (Concept: The Journal of Contemporary Community Education Practice Theory, 2025)
Education can and should be emancipatory. Yet, for many of our neurodivergent children, it can feel like torture. Common challenges faced by neurodivergent children in our schools include sleep deprivation, sensory overload, social isolation, and repeated questioning - all compounded by a sense of powerlessness and the inability to leave or change their environment. As much as we strive to do our best for our young, it sometimes feels as though, in our efforts to educate, we do more harm than good.There is no doubt that we’ve made significant progress in supporting neurodivergent children. It wasn’t so long ago that some children were forced to write with their non-dominant hand or subjected to physical punishment for failing to make the grade. However, despite this progress, inequality of outcomes for neurodivergent individuals persists. In extreme cases, some are even institutionalized in hospitals, or imprisoned due to a lack of appropriate and available support. Clearly, we still have a long way to go. Given the chronic underfunding of our education system, it feels increasingly important for individuals to come together, support one another, and collectivize their efforts for change. This poem is not about any one person. It is an amalgamation of my own experiences—as a child, parent, husband, educator, and a friend and confidant to other parents of neurodivergent children. I’ve been fortunate to be part of a self-organized parent support group for adults with neurodivergent children. There is something deeply powerful about learning from others with shared or similar experience - helping and being helped at the same time. Sometimes, it feels like you don’t have the energy to take on another responsibility, another evening spent meeting with other parents. But, in my experience, it is almost always worth it. The connection with others, the empathy for each other’s situations - it all helps to re-energize you for the fight ahead. As one of my fellow strugglers once said, 'I arrive with a problem, but always leave with a few new ideas to try and address it'.  Moreover, participation in interest groups provides opportunities for collective action in support of our cause. This poem was used as a means of sharing the experiences of neurodivergent children with their teachers.This poem is dedicated to the parents and carers of neurodivergent children, their allies within the education system (of which there are many), and to all the neurodivergent children making their way through the school day - after day, after day.